Pengaruh Persepsi Manfaat Dan Persepsi Kemudahan Penggunaan Terhadap Keputusan Pembelian Pada Tiktok Shop - Sri Astuti; Almansyah Rundu Wonua; Andry Stepahnie Titing (Sekolah Tinggi Ilmu Administrasi Yappi Makassar Jl. Sumba no 46, Kota Makassar, Sulawesi Selatan, 2023)
The purpose of this study was to determine: (1) The effect of perceived usefulness on purchasing decisions (study of management students at the University of Nineteen November Kolaka). (2) The Effect of Perceived Ease of Use on Purchasing Decisions (Study on Management Students at the University of Nineteen November Kolaka. This research uses a quantitative method approach. Data collection in this study uses observation and questionnaires. The population of this study is management students class 2018-2022. Meanwhile The sample of this research is 84 respondents by determining the sample using probability sampling technique.The data analysis technique used in this research is Structural Equation Modeling (SEM) based on Partial Least Square (PLS) through measurement model test (outer model) and structural model test (inner model) with Smart PLS 3.0. Based on the research results it is known that the Perceived Usefulness variable has a positive and significant effect on Purchase Decisions as indicated by the P-Values ​​of 0.049. As well as the Perceived Ease of Use variable also has a positive and significant effect on Purchase Decisions this is indicated by the value P-Values ​​of 0.000.